Added value of high-risk plaque criteria by coronary CTA for prediction of long-term outcomes. (May 2020) - Senoner, Thomas; Plank, Fabian; Barbieri, Fabian; Beyer, Christoph; Birkl, Katharina; Widmann, Gerlig; Adukauskaite, Agne; Friedrich, Guy; Dichtl, Wolfgang; Feuchtner, Gudrun M.
Abstract: Background and aims: Long-term data relating coronary computed tomography angiography (CTA) to coronary artery disease (CAD) prognosis including novel CTA-biomarkers ("high–risk plaque criteria") is scarce. The aim of this study was to define predictors of long-term outcomes. Methods: 1430 low-to-intermediate risk patients (57.9 ± 11.1 years; 44.4% females) who underwent CTA and coronary calcium scoring (CCS) were prospectively enrolled. CTAs were evaluated for (1) stenosis severity CADRADS 0–4 (minimal <25%, mild 25–50%, moderate 50–70%, severe >70%), (2) mixed plaque burden weighted for non-calcified plaque (NCP), and (3) high-risk-plaque (HRP) criteria: low-attenuation-plaque (LAP), napkin-ring-sign, spotty calcifications <3 mm or remodeling index >1.1. Endpoints were all-cause and cardiovascular mortality, composite fatal and nonfatal major adverse cardiovascular events (MACE). Results: Over a mean follow-up of 10.55 years ± 1.98, 106 patients (7.4%) died, 25 from cardiovascular events (1.75%). Composite MACE occurred in 57 (3.9%) patients. In patients with negative CTA, cardiovascular mortality and MACE rates were 0% and 0.2%. Stenosis severity by CTA predicted all 3 endpoints ( p  < 0.001) while CCS >100 AU predicted only all-cause mortality ( p  = 0.045) but not MACE. The high risk plaque criteria LAP <60HU (HR: 4.00, 95%CI 95% 1.52–10.52, p  = 0.005) and napkin-ring (HR 4.11, CI 95% 1.77–9.52, p  = 0.001) predicted MACE but not all-cause-mortality, after adjusting for risk factors, while spotty calcification and remodeling index did not. Similarly, mixed plaque burden predicted MACE ( p  < 0.0001). HRP criteria, if added to CADRADS + CCS for prediction of MACE, were superior to CCS (c = 0.816 vs 0.716, p < 0.001). In 33.5% of CCS zero patients, non-calcified fibroatheroma were found. Conclusions: Long-term prognosis is excellent if CTA is negative for CAD. The high-risk plaque criteria LAP<60HU and napkin-ring-sign were independent predictors of MACE while HRP criteria added incremental prognostic value. Graphical abstract: Image 1 Highlights: High-risk plaque criteria are associated with increased morbidity and mortality. Stenosis severity by computed tomography angiography (CTA) predicts all-cause and cardiovascular mortality. Plaque burden, low-attenuation-plaque (LAP) <60HU and napkin-ring predict major adverse cardiovascular events (MACE), but not all-cause mortality. Patients with negative CTA for coronary artery disease have an excellent long-term prognosis.